Dampak Perang terhadap Kemanusiaan dan Ketahanan Pangan dalam Film Grave of the Fireflies (1988): The Impact of War on Humanity and Food Security in the Film Grave of the Fireflies (1988) - Azizah, Anindya Putri; Yumitro, Gonda (Anterior Jurnal, 2024)
This study uses the Japanese animated film "Grave of the Fireflies" (1988) as a case study to analyze the impact of war on humanity and food security. The film "Grave of the Fireflies" is important to observe from a humanitarian and food security perspective because it depicts in depth the tragic experiences of civil society during the war period, as well as highlighting the challenges faced by civil society in meeting basic needs such as the food crisis during the war. This article aims to conduct a descriptive analysis of the impact of war on humanity and food security in the film "Grave of the Fireflies". In this research, data was collected through two main sources. First, analyze the film by watching and observing the film and taking dialogue excerpts that are relevant to the research. Second, the analysis uses research data based on the Scopus database with the keywords "World War II", "Humanity", and "Food Security". Data collected from 446 journals from the Scopus database was analyzed using the Nvivo 14 plus application. The research results show that in the film "Grave of the Fireflies" there is a humanitarian impact of war, namely, the misery of civilians, loss of homes, and jobs, and deep fear. Meanwhile, the impact on food security is that countries tend to experience food crises during war. The impact of the war on food supplies was minimal and food became scarce due to limited access during the war. This causes malnutrition and even death.